Artificial Intelligence Use as Communication Media in Learning Activity for Senior High School - Nofha Rina (Lingkar Studi Komunikasi (LISKI), 2023)
The influence of AI technology in teaching and learning at school has become an objective issue for identifying the utilization of AI as a medium of communication learning based project to the student in Senior High School. In this research, the data analysis used by quantitative and qualitative methodology for the sake of achievement the purpose of this. Quantitative data analyzed using paired samples t-test to know how far is learning based project can influence student attitude in activity learning. In addition, qualitative data was also analyzed with objective to observe how learning-based project affect the learning process students implemented in online atmosphere. There are 40 students of 11th grade at State Senior High School of 46 (SMAN 46) in the Cibiru District who participated in the study. The finding shown that they are satisfied in the use of AI at the learning activities. Keywords: Artificial Intelligence, Learning Activity, Students, Communication Media